Asociación del control glicémico con el conocimiento sobre diabetes mellitus tipo 2 y la adherencia al tratamiento en pacientes adultos con diabetes mellitus tipo 2 - Morales Ruiz, Sigifredo Alexis (2020)
Objective:Determinate association level between glycemic control withtype 2 diabetes mellitus knowledge and treatment adherence in adults patients with type 2 diabetes mellitus. Method:A correlational cross-sectional non-experimental study was conducted, with a sample size of 100 patients diagnosed with Type 2 Diabetes Mellitus. Chi-square statistic method was used to determinate if there were association between the variables. Information was ordered in a database, processed and analyzed in the statistic program IBM SPSS Statistics 21. Results:Has been found 52 patients with poor glycemic control (52%) and 48 with good glycemic control (48%). Association between level Knowledge and glycemic control, Chi-square 0.306 (p=0.858). Association between Treatment adherence and glycemic control, Chi-square 1.182 (p=0.178). Conclusion:There’s no association between glycemic control, and Type 2 diabetes mellitus knowledge and Treatment adherence.